One-pot cascade syntheses of microporous and mesoporous pyrazine-linked covalent organic frameworks as Lewis-acid catalysts. Issue 21 (29th March 2019) - Ma, Yunchao; Liu, Xiaozhou; Guan, Xinyu; Li, Hui; Yusran, Yusran; Xue, Ming; Fang, Qianrong; Yan, Yushan; Qiu, Shilun; Valtchev, Valentin
Abstract : Covalent organic frameworks (COFs) are crystalline porous solids with broad potential applications. Abstract : Covalent organic frameworks (COFs) are crystalline porous solids with broad potential applications. So far, the successful construction of COFs has been limited to a few condensation reactions, and nearly all COFs were obtained by single-step synthesis based on predesigned linkers. Here, we report a general strategy in view of a one-pot cascade reaction to prepare both microporous and mesoporous fully π-conjugated pyrazine-linked COF materials (PZ-COFs). The obtained PZ-COFs show high chemical stability, large specific surface areas and promising H2, CH4 and CO2 uptake capacities. Furthermore, we demonstrate that manganese(ii )-incorporated PZ-COFs can act as excellent Lewis-acid catalysts for the cyanosilylation of aromatic aldehydes. This study not only provides a facile method to synthesize COFs required for multistep reactions but also expands the applications of COFs as promising catalysts.